PENGATURAN PENGGUNAAN GANJA SEBAGAI BAHAN BAKU PRODUKSI OBAT - Riviera Constine Marainaya; Yovita Arie Mangesti (Gapenas Publisher, 2023)
Marijuana is used for medicinal purposes because it contains several chemical compounds that can cure various diseases. It was explained that cannabis is included in a type of narcotics class 1 because it contains tetrahydrocannabinol (THC), in the Narcotics Law that the term